The role of relationship marketing dimensions in the customer retention - Žvirelienė, Renata; Bučiūnienė, Ilona (Business: Theory and Practice, 2008)
Advancement of science and technology, growth of service sector, strengthening of competition and, what is the most important, diversity of customer needs and regular changes thereof, determined the necessity for a new approach to the development of operations. Relationship marketing is defined as “the new marketing”, oriented towards the main objective of the company’s operations – fulfillment of customer needs and building of long-term relationships with customers. However, loyalty from the customers’ side is not guaranteed. customer’s wish to maintain loyal relationships depends on the company’s ability to foresee the needs of potential customers and to fulfil them before the competitors do that. A company that seeks to earn the customer loyalty and maintain a competitive advantage has to be well versed in the qualitative dimensions of relationships – the main principles for maintaining of relationships.As shown in the analysis of scientific literature on the subject of relationship marketing, only a few of scientific researches were devoted to operationalization of the key dimensions of relationship marketing. After taking into consideration the interpretations of commentation on relationship marketing dimensions, presented by the scholars, and their significance to the company’s relationships with business partners, the following main relationship marketing dimensions were identified: empathy, communication, cooperation, satisfaction, trust and commitment. Manifestation of these dimensions in conjunction with formal measures of the company such as organizational rules of behaviour and the code of ethics determine the strength and development of relationships between the parties that maintain them. Empirical research into manifestation of relationship marketing dimensions in relationships of cargo vehicles manufacturers’ representative offices with their customers allowed to establish that the manifestation of relationship marketing dimensions in relationships of these companies with customers was sufficiently strong and in turn determined closeness of these relationships. Article in Lithuanian. Santykių marketingo dimensijų vaidmuo išlaikant vartotojus Santrauka. Mokslo ir technikos pažanga, paslaugų sektoriaus augimas, stiprėjanti konkurencija, o svarbiausia vartotojų poreikių įvairumas bei nuolatiniai jų pokyčiai lėmė naujo požiūrio į veiklos plėtotę būtinumą. Santykių marketingas apibūdinams kaip naujasis marketingas, kuris orientuotas į pagrindinį įmonės veiklos tikslą – vartotojų poreikių tenkinimą ir ilgalaikių santykių su vartotojais kūrimą. Kaip įmonei pavyksta hiperkonkurencinėje rinkoje užmegzti ir palaikyti glaudžius santykius tiek su vartotojais, tiek su kitais rinkos subjektais, priklauso nuo to, kaip įmonė gerai išmano santykių marketingo dimensijas – pa-grindinius santykių palaikymo principus. Reikšminiai žodžiai: santykių marketingas, įmonės santykiai su vartotojais, vartotojų išlaikymas, santykių marketingo dimensijos, pasitenkinimas, pasitikėjimas, įsipareigojimas. First published online: 22 Dec 2008